Measuring the Legality of Cryptocurrencies in the Fatwas - ., Andi Yaqub (Al-'Adl, 2023)
Review of legality regarding the existence and use of cryptocurrencies from an Islamic legal perspective focusing on fatwas. The finding Content analysis and comparison on references and istinbath methods in drawing conclusions. Policy regarding crypto in Indonesia has not accommodated legal protection and certainty to anticipate elements of speculation in crypto transactions and differences in scholarly decisions on crypto are caused by different sources of reference and understanding of sil'ah and currency. The legal status of transactions using Cryptocurrency is determined to be haram if there is gharar, maysir, and allows cryptocurrency to be used as an instrument of speculation and is determined mubah if it meets the sil'ah category and there is certainty that can eliminate all potential haram then cryptocurrency as a legal currency is used